Occupation Health and Safety: A Failure to Protect the Right of Workers to Participate in Enforcement - King, Andrew; Lewchuk, Wayne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2022)
SummarySection 50 of the Ontario Occupational Health and Safety Act prohibits an employer from punishing a worker who complains about a health and safety concern and who seeks to exercise the right to raise or report this concern. A worker who suffers such a reprisal may file a grievance if covered by a collective agreement or make an application to the Ontario Labour Relations Board (OLRB).We studied the effectiveness of this protection by reviewing 688 OLRB section 50 complaint cases that had been filed and concluded between 2006 and 2017 and by interviewing 25 workers who had suffered reprisals and completed a formal complaint or grievance.The majority of the workers had filed complaints about a physical work hazard. There was alleged harassment and/or violence in 45% of the cases. There was harassment in half of the cases involving women. Employment was frequently terminated when the complainants had exercised their legal right to refuse unsafe work, to call an inspector or to act as a worker OHS representative.Although government OHS inspectors played a key role in most cases when called to address occupational health and safety concerns, they were prevented by government policy from investigating the reprisals. There was no penalty for employers who had violated section 50.In the vast majority of cases, the complaints were settled without reinstatement of the worker and with an average settlement of $5,461. The complainant had to accept a confidentiality agreement as part of the settlement.While the current settlement system is unlikely to encourage workers to exercise their rights, it does provide some compensation for those who have exercised them. In many of the cases we examined, the reprisal victims were faced with serious risks to their health and safety. They were not faced with a choice so much as a necessity to act. Often, they used strategies that could have been more effective in a system that recognized and defended their rights. Although the settlements were inadequate in recognizing both the rights at stake and the victims’ sacrifices, many of these workers did benefit from that option. Given that inspectors had responded to most of the complaints and investigated them, there is a basis for more effective enforcement.AbstractWorkers have a right to participate in enforcement of occupational health and safety. Using a review of 688 cases submitted to the Ontario Labour Relations Board (OLRB) and 25 in-depth interviews with workers who went through the process, we examined the state’s strategy to protect workers from employer reprisals when they exercise health and safety rights at work. We argue that the existing remedies are important but limited and should be enhanced by a strategy of enforcing workers’ participation rights through sanctions directed against specific employer behaviours. In particular, the state should sanction employer harassment that masquerades as supervision.